Representation of Contemporary Javanese Femininity in Tikok Rania Yamin's Content @raniaayamin (John Fiske's Semiotic Model Study) - Putri Dwi Ramadhani (International Journal of Social, Economic, and Business, 2025)
Femininity is often associated with stereotypes of female behavior, appearance, and gender roles that have been passed down from generation to generation. One interesting phenomenon is how Tiktok is used to build and voice narratives about Javanese femininity in the modern era such as on Rania Maheswari Yamin's Tiktok account @raniaayamin. This study uses John Fiske's theory of representation and semiotic analysis and aims to analyze the representation of Javanese femininity in Rania Yamin's Tiktok content, namely on the @raniaayamin account and reveal how social media such as Tiktok can be an effective platform in exploring the relevance of Javanese femininity amidst the development of modernity. The results of this study are that Rania Yamin shows that she does not simply use her identity as a member of the palace family for personal or branding purposes, but consciously positions herself as an active cultural representation as a cultural agent who bridges between tradition and the younger generation.